2022
DOI: 10.1002/adfm.202202184
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Synergistic Enhanced Self‐Powered Photodetector via Multi‐Effect Coupling Strategy toward High‐Efficiency Ultraviolet Communication

Abstract: Ultraviolet (UV) communication is a promising security optical wireless communication technology, and self‐powered photodetectors as their optical receivers offer formidable evolution opportunities. However, insufficient light harvesting and carrier separation of self‐powered photodetectors hinder them from achieving high‐efficiency UV communication. Herein, a multi‐effect coupling strategy is proposed to design an enhanced self‐powered Ag NPs@ZnO nanowires/PEDOT:PSS (AZP) UV photodetector. Taking full advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Especially, the polarity of the photocurrent at a zero voltage exhibits a large dependence on the laser wavelength, leading to the bipolar spectral photoresponse. Under visible (Vis) 405 nm illumination, the photocurrent is negative, which is similar to other results induced by the PV effect. , However, the photocurrent becomes positive under infrared (IR) 1550 nm illumination, and the polarity is reversed, implying that the photoresponse could be charged by a new physical mechanism when the light irradiation is changed from 405 to 1550 nm wavelength.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Especially, the polarity of the photocurrent at a zero voltage exhibits a large dependence on the laser wavelength, leading to the bipolar spectral photoresponse. Under visible (Vis) 405 nm illumination, the photocurrent is negative, which is similar to other results induced by the PV effect. , However, the photocurrent becomes positive under infrared (IR) 1550 nm illumination, and the polarity is reversed, implying that the photoresponse could be charged by a new physical mechanism when the light irradiation is changed from 405 to 1550 nm wavelength.…”
Section: Resultssupporting
confidence: 80%
“…Under visible (Vis) 405 nm illumination, the photocurrent is negative, which is similar to other results induced by the PV effect. 35,36 However, the photocurrent becomes positive under infrared (IR) 1550 nm illumination, and the polarity is reversed, implying that the photoresponse could be charged by a new physical mechanism when the light irradiation is changed from 405 to 1550 nm wavelength. Figure 2d further presents the dynamic photoresponse behaviors of the heterojunction under 405 and 1550 nm irradiation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…R A can be calculated by R A = I photo /P , where I photo ( I photo = I light −I dark ) denotes to the photocurrent and P is the incident light intensity. [ 34 ] The 5%KCQDs PDs possess the most excellent responsivity of 0.375 A W −1 , which is three times of the CQDs PDs. When current noise assumes only come from dark current, D * can be expressed as the formula of D* = R A / (2 qJ d ) 1/2 , where q is the elementary charge and J d is the dark current density.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various energy detection systems, presently, ultraviolet-visible (UV-Vis) self-powered photodetectors (PDs) have found widespread application in wireless control systems/communication, [1,2] biological/chemical analysis [3,4] visual-image Self-powered photodetectors (PDs) have been recognized as one of the developing trends of next-generation optoelectronic devices. Herein, it is shown that by introducing a thin layer of SnO film between the Si substrate and the ZnO film, the self-powered photodetector Al/Si/SnO/ZnO/ITO exhibits a stable and uniform violet sensing ability with high photoresponsivity and fast response.…”
Section: Introductionmentioning
confidence: 99%